2009
DOI: 10.1073/pnas.0907425106
|View full text |Cite
|
Sign up to set email alerts
|

A genetic variation of the noradrenergic system is related to differential amygdala activation during encoding of emotional memories

Abstract: Emotionally arousing events are typically well remembered, but there is a large interindividual variability for this phenomenon. We have recently shown that a functional deletion variant of ADRA2B, the gene encoding the ␣2b-adrenergic receptor, is related to enhanced emotional memory in healthy humans and enhanced traumatic memory in war victims. Here, we investigated the neural mechanisms of this effect in healthy participants by using fMRI. Carriers of the ADRA2B deletion variant exhibited increased activati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
120
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(128 citation statements)
references
References 60 publications
7
120
1
Order By: Relevance
“…Furthermore, this finding indicates that carriers of this deletion are more strongly affected by stressful events. It has been shown that carriers of the ADRA2B deletion display increased amygdala activity while encoding arousing negative pictures, but not when encoding less-arousing positive pictures (25). This suggests that the neural effects of this genotype are dependent on arousal.…”
mentioning
confidence: 91%
“…Furthermore, this finding indicates that carriers of this deletion are more strongly affected by stressful events. It has been shown that carriers of the ADRA2B deletion display increased amygdala activity while encoding arousing negative pictures, but not when encoding less-arousing positive pictures (25). This suggests that the neural effects of this genotype are dependent on arousal.…”
mentioning
confidence: 91%
“…Moreover, trauma survivors with the ADRA2B deletion variant are more likely to reexperience traumatic events (6). Following up on these findings, the results reported by Rasch et al (2) are the first to tie the deletion variant of the gene to patterns of amygdala activation during the encoding of emotional memories. Across all participants, the most arousing images were most remembered 10 min later in a subsequent free recall task.…”
mentioning
confidence: 49%
“…Further, why are some of us more likely to remember emotional memories with Proustian vividness than others or more likely to relive traumatic events? Echoing Proust's thesis that one's emotional memories are closer to the heart than to the mind, a study in this issue of PNAS by Rasch et al (2) suggests that individual differences in the ADRA2B gene that codes the ␣2B adrenoreceptor, which plays an important role in vasoconstriction and blood pressure regulation, is also related to brain activation patterns underlying heightened emotional recall.…”
mentioning
confidence: 99%
“…Evidence suggests that affective reactivity in the amygdala may be influenced by several monoamine systems, including serotonin (5-HT), norepinephrine (NE), and dopamine (DA; Costafreda et al, 2013;Cousijn et al, 2010;Dannlowski et al, 2010;Delaveau et al, 2009;Rasch et al, 2009). Initially, a simple lack of monoamines was thought to cause depressive symptoms, however the role of monoamines in MDD has been shown to be much more complex than this (Delgado, 2000;Hirschfeld, 2000).…”
Section: The Role Of Amygdala Function In Depressionmentioning
confidence: 99%